2015
DOI: 10.1111/ecin.12254
|View full text |Cite
|
Sign up to set email alerts
|

More Mortgages, Lower Growth?

Abstract: In newly collected data on 46 economies over 1990-2011, we show that financial development since 1990was mostly due to growth in credit to real estate and other asset markets, which has a negative growth coefficient. We also distinguish between growth effects of stocks and flows of credit. We find positive growth effects for credit flows to nonfinancial business but not for mortgage and other asset market credit flows. By accounting for the composition of credit stocks and for the effect of credit flows, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 71 publications
(157 reference statements)
8
58
0
Order By: Relevance
“…The correlation with GDP per capita is significant and strongly negative in both FE and system-GMM regressions. This result sheds some light on recent finance-growth findings (Arcand et al, 2015;Bezemer et al, 2016). If lower business credit shares are one feature of more financial development, then it is understandable that more financial development is not necessarily 'good for growth', given the fact that it is business credit, not household credit, which drives the finance-growth relation (Beck et al, 2012).…”
Section: Estimation Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The correlation with GDP per capita is significant and strongly negative in both FE and system-GMM regressions. This result sheds some light on recent finance-growth findings (Arcand et al, 2015;Bezemer et al, 2016). If lower business credit shares are one feature of more financial development, then it is understandable that more financial development is not necessarily 'good for growth', given the fact that it is business credit, not household credit, which drives the finance-growth relation (Beck et al, 2012).…”
Section: Estimation Resultsmentioning
confidence: 60%
“…They build a similar cross-country dataset to ours, with smaller country coverage and shorter time span, including a broad distinction between household and business credit. Beck et al (2012) find that household credit has negligible growth effects, a finding confirmed by Bezemer et al (2016).…”
Section: Differentiating Bank Credit: Relevance To Growth Stability mentioning
confidence: 80%
See 1 more Smart Citation
“…There is an increasing recognition of the critical role rising household debt plays as a cause of financial crises (Bezemer et al 2016;Bezemer & Grydaki 2014;Schularick & Taylor 2012;Mian & Sufi 2009). However there is still relatively little systematic empirical research on the reasons for the spectacular rise of household debt in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…The costs to income growth were large. Torsten Beck et al (2012), Bezemer, Grydaki, and Zhang (2016), and Jordà, Taylor, and Schularick (2014) all show with advanced statistical analysis that the contribution of household credit to income growth has become Finance Is Not the Economy 755 negligible or is plainly negative. Last year, IMF and OECD reports made the same point (Sahay et al 2015;Cornede, Denk and Hoeller 2015).…”
Section: Empirical Evidencementioning
confidence: 99%